A CLASSROOM ACTION RESEARCH: THE USE OF CHAIN DRILL-SIMULATION FOR TEACHING SPEAKING - Henry Elisa; Sijono Sijono; Veronika Vika Bintang; Maria Viani (Journal of English Educational Study (JEES), 2023)
This research investigates the utility of chain drill simulations as a pedagogical technique for enhancing speaking proficiency among junior high school students in Sintang, West Kalimantan. Speaking skills are a vital aspect of language education, and this study assesses the potential of structured speaking exercises to bolster students' communication abilities. Through the implementation of chain drill simulations in the classroom, accompanied by feedback and assessment, the research demonstrates that this approach offers an engaging platform for students to practice and develop their speaking skills. Additionally, the adaptability of the technique to cater to students with varying language proficiency levels is highlighted. The study underscores the importance of constructive feedback and assessment in facilitating students' speaking skill growth. While supporting the use of chain drill-simulations as a valuable tool for teaching speaking skills at the junior high school level, the research emphasizes the need for ongoing assessment and further refinement to optimize this technique. The findings have implications for language education in the local context of Sintang, recognizing the role of effective communication in students' academic and personal development.